Effect of Addition Amount on Rheological, Structural, and Sensory Properties of Whole-Grain Sweet Potato Noodles Using Extrusion - Yan Zeng; Jie Wang; Mengxiao Bao; Yue Wu; Zhigang Chen (Foods)
Whole grain foods have been recommended to preserve biologically active components and benefit human health. The effect of the addition amount of whole sweet potato flour (WSPF, 25%, 51%, and 75%) on the physicochemical and structural properties of extruded whole-grain noodles was evaluated. Compared with traditional wheat flour (WF), the increased content of WSPF led to an enhancement in the dough’s water retention capacity, resulting in the reduction of dough development time and stability time. The modulus of elasticity and the modulus of loss of the dough exhibited a positive correlation with the proportion of WSPF added, while the tangent value and maximum creep flexibility were negatively correlated. Confocal laser scanning microscopy (CLSM) observed that WSPF induced protein aggregation in the dough. Compared to conventional WF, the increased incorporation of WSPF resulted in improved textural characteristics of the extruded noodles. Sensory evaluation indicated that the addition of WSPF could enhance the quality of the noodles by imparting a sweet potato aroma, a distinctive color, and a satisfactory taste. These characteristics were correlated with their enhanced relative crystallinity, enthalpy, and short-range ordered structure. Additionally, 75% whole-grain sweet potato noodles exhibited the highest relative crystallinity (11.05%), enthalpy of pasting (ΔH, 22.6 J/g), and short-range ordered structure (0.78). SEM results indicated that the presence of holes in the cross-section of the sweet potato extruded noodles facilitated their rapid rehydration. Overall, the whole-grain sweet potato noodles have great potential in promoting the textural, sensory, and nutritional properties compared to traditional wheat noodles.